Quantification of neuroinflammation in spinal cord and neuroforamina of patients with painful cervical radiculopathy using [11C]DPA713 PET/CT - Lutke Schipholt, Ivo J.; Scholten-Peeters, Gwendolyne G. M.; Koop, Meghan A.; Coppieters, Michel W.; Boellaard, Ronald; van de Giessen, Elsmarieke; ter Meulen, Bastiaan C.; Coenen, Marieke; Vleggeert-Lankamp, Carmen; Depaauw, Paul R.; van Berckel, Bart N. M.; Lammerstma, Adriaan A.; et al. (Frontiers in Nuclear Medicine, 2025)
BackgroundAnimal models of nerve compression have revealed neuroinflammation not only at the entrapment site, but also remotely at the spinal cord. However, there is limited information on the presence of neuroinflammation in human compression neuropathies. The objectives of this study were to: (1) assess which tracer kinetic model most optimally quantified [11C]DPA713 uptake in the spinal cord and neuroforamina in patients with painful cervical radiculopathy, (2) evaluate the performance of linearized methods (e.g., Logan) and simplified (e.g., standardized uptake value - SUV) methods, and (3) assess the test-retest reliability of these methods. Microglia activation associated with neuroinflammation was quantified using positron emission tomography (PET) with the radiotracer [11C]DPA713, targeting the 18 kDa translocator protein (TSPO). The Akaike information criterion, visual inspection of the fits and number of outliers were used to select the optimal kinetic model. As unaffected tissue, the spinal cord and neuroforamina three cervical levels above the affected target tissue was used.ResultsThe single tissue (1T2k) compartment model was the preferred model to describe [11C]DPA713 kinetics at the spinal cord and neuroforamina. Higher levels of 1T2k VT were observed in the affected neuroforamina and spinal cord compared with corresponding unaffected tissues. Logan VT (≥0.73) showed high correlation with 1T2k VT at both locations. Of the simplified methods, neuroforamina and spinal cord SUV normalized for the metabolite corrected plasma (TBR-PP) exhibited high correlations with 1T2k VT (r ≥ 0.84). Test-retest reliability varied between fair to excellent.ConclusionsThese results indicate that a 1T2k model with metabolite corrected image derived input function can be used to describe the kinetics of [11C]DPA713 in the spinal cord and neuroforamina in humans. 1T2k VT or Logan VT can be used as binding metric, while TBR-PP is the recommended choice among simplified models.